Strengthening Dominus Litis Principle for Effective Corruption Case Management in Indonesia: Harmonizing Positive Law and Islamic Legal Principles - Zet Tadung Allo; M. Syukri Akub; Aswanto Aswanto; Ratnawati Ratnawati; Andi Muhammad Aswin Anas (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2025)
Corruption in Indonesia persists as a systemic problem, exacerbated by fragmented investigative authority, inconsistent regulations, and the absence of strict deadlines for case resolution. This study examines the dominus litis principle—vesting the Prosecutor’s Office with control over criminal cases—through both Islamic legal foundations and empirical realities in Indonesia. Using a normative-empirical method that combines legislative, conceptual, and comparative analyses, the research highlights the novelty of contextualizing dominus litis within Islamic jurisprudence, constitutional mandates, and human rights principles. Islamic sources, including the Qur’an and Hadith, unequivocally condemn corruption as ghulūl and bribery, framing it as both a sin and a betrayal of public trust. From the perspective of maqāṣid al-sharī‘ah, prolonged investigations that freeze assets and stigmatize suspects create harm (mafsadah) rather than benefit (maṣlaḥah), thereby violating the objectives of justice, dignity, and wealth protection. Historical institutions such as the qāḍī al-maẓālim and the doctrine of siyāsah shar‘iyyah further legitimize prosecutorial oversight as a means of ensuring accountability and safeguarding public welfare. Empirical evidence shows that fragmented authority between the Police, the Corruption Eradication Commission (KPK), and the Prosecutor’s Office has caused overlapping roles, case stagnation, and human rights violations. Comparative insights from civil law jurisdictions such as Germany and France illustrate that stronger prosecutorial dominance ensures legal certainty and efficiency. The study concludes that reinforcing the Prosecutor’s Office as dominus litis from the investigation stage is essential for harmonizing institutional roles, establishing strict case deadlines, and enhancing coordination. Contextualized within Islamic law and Indonesian constitutional values, dominus litis emerges not only as a procedural reform but also as a structural solution that integrates legal certainty, justice, and moral legitimacy in Indonesia’s fight against corruption